2022
DOI: 10.3390/ma15020488
|View full text |Cite
|
Sign up to set email alerts
|

Durability Performance of Self-Compacting Concrete Containing Crumb Rubber, Fly Ash and Calcium Carbide Waste

Abstract: Waste tire disposal continues to pose a threat to the environment due to its non-biodegradable nature. Therefore, some means of managing waste tires include grinding them to crumb rubber (CR) sizes and using them as a partial replacement to fine aggregate in concrete. However, the use of CR has a series of advantages, but its major disadvantage is strength reduction. This leads to the utilization of calcium carbide waste (CCW) to mitigate the negative effect of CR in self-compacting concrete (SCC). This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…According to this case, sustainable and greener production of construction technologies and eco-friendly evaluation of industrial by-products are current issues [ 35 ]. There have been lots of studies about the usage of industrial by-products as a replacement material against cement for the production of SCC [ 36 , 37 , 38 , 39 , 40 ]. This study is focused on the fine aggregate replacement effect on the fresh and hardened properties of SCC mixtures.…”
Section: Research Gapmentioning
confidence: 99%
“…According to this case, sustainable and greener production of construction technologies and eco-friendly evaluation of industrial by-products are current issues [ 35 ]. There have been lots of studies about the usage of industrial by-products as a replacement material against cement for the production of SCC [ 36 , 37 , 38 , 39 , 40 ]. This study is focused on the fine aggregate replacement effect on the fresh and hardened properties of SCC mixtures.…”
Section: Research Gapmentioning
confidence: 99%
“…Adamu et al showed that using calcium carbide residue along SCM can reduce cement consumption in concrete [ 5 ]. Kelechi et al also confirmed the better durability of such carbides [ 6 ]. Researchers used different carbides in various forms, e.g., nanoparticles, powder, and flakes or fibers.…”
Section: Introductionmentioning
confidence: 85%
“…The increase in weight reduction due to H 2 SO 4 and MgSO 4 CR immersion can be traced to the increased voids initiated by the CR in the cement pattern due to air entrainment during mixing. These voids in the strong cement pattern expand easily in the acidic environment causing deterioration of the cement paste and higher weight reduction [44].…”
Section: Durability Performance Against Acid and Salt Attackmentioning
confidence: 99%
“…Additionally, the decrease in salt resistance due to CR was due to the high pores in the hardened cement matrix resulting from the air entrapped on the surface of the CR during mixing. This increased the internal pressure on the cement matrix by the sulfate-related growth crystals, causing internal cracks and hence deterioration of the cement paste [44,45]. Furthermore, a large amount of crystals produced in the pores of the matrix by the salt solution causes large crystallization pressure causing deterioration of the cementitious matrix [46].…”
Section: Elevated Temperaturementioning
confidence: 99%